PENATAAN PASAR PAGI WAHIDIN DI JALAN Dr. WAHIDIN SUDIROHUSODO KELURAHAN SUNGAI BANGKONG KECAMATAN PONTIANAK KOTA KOTA PONTIANAK: PENATAAN PASAR PAGI WAHIDIN DI JALAN Dr. WAHIDIN SUDIROHUSODO KELURAHAN SUNGAI BANGKONG KECAMATAN PONTIANAK KOTA KOTA PONTIANAK - Marwan, Abang; muhtadi, ahmad (Jurusan Teknik Sipil Polnep, 2022)
The market is a place for trading activities and can be said to be good if it has adequate facilities andinfrastructure. The Wahidin Morning Market still has shortages ranging from stalls, parking, drainage, TPS, andwaste water. The method used is to find data about the city of Pontianak, population data around the market, andthe condition of facilities and infrastructure in the market. Therefore, it is planned to arrange the market startingfrom stalls, parking, drainage, TPS, clean water, and waste water. The analysis starts from the layout of the stallsor kiosks, parking calculations, drainage calculations, waste treatment systems, clean water needs, andwastewater treatment systems. - condiments, furniture and fruits. The middle section contains vegetable tradersand the back contains meat traders. Parking with a total area of 195 m2. The drainage design is divided into threedifferent sizes. The waste system, namely the trash can is divided into two types, organic and inorganic. The cleanwater system uses a reservoir. The WWTP (Wastewater Treatment Plant) system uses an Anaerobic-AerobicBiofilter. The Wahidin Morning Market is planned to have 52 stalls with a parking capacity of 6 cars and 50motorbikes. The waste system is that organic waste is made into compost and inorganic waste is taken byscavengers and sold.